2011
DOI: 10.1016/j.bpc.2011.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Polycation induced actin bundles

Abstract: Three polycations, polylysine, the polyamine spermine and the polycationic protein lysozyme were used to study the formation, structure, ionic strength sensitivity and dissociation of polycation-induced actin bundles. Bundles form fast, simultaneously with the polymerization of MgATP-G-actins, upon addition of polycations to solutions of actins at low ionic strength conditions. This indicates that nuclei and/or nascent filaments bundle due to attractive, electrostatic effect of polycations and the neutralizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(46 citation statements)
references
References 47 publications
(64 reference statements)
2
44
0
Order By: Relevance
“…Data for F-actin taken from 30, 49 , for CSA13 from 67 , LL37 from 94, 99 , vimentin from 82, 114 , Pf1 from 12 , fd from 115 , Lys18 from 30 , F-actin/spermine from 14 , DNA and spermine from 116 , DNA and cobalt hexamine from 117 .…”
Section: Figurementioning
confidence: 99%
“…Data for F-actin taken from 30, 49 , for CSA13 from 67 , LL37 from 94, 99 , vimentin from 82, 114 , Pf1 from 12 , fd from 115 , Lys18 from 30 , F-actin/spermine from 14 , DNA and spermine from 116 , DNA and cobalt hexamine from 117 .…”
Section: Figurementioning
confidence: 99%
“…It must be noted that in some instances some actin bundling appeared when eEF1A was not present. This is not unusual, as there is a large body of literature showing that, due to the polyelectrolyte nature of F-actin, bundles can form without the presence of specific actin binding proteins (Tang et al, 1997(Tang et al, , 2001Xian et al, 1999;Angelini et al, 2003;Muhlrad et al, 2011). However, these bundles differed from those which were formed due to the presence of eEF1A in that there were less of them and they were somewhat smaller in diameter Interestingly, we found that, when phalloidin was not present but eEF1A was AFM images still revealed the presence of intact F-actin filaments exhibiting bundling, thus indicating that eEF1A has some stabilising affect on F-actin.…”
Section: Discussionmentioning
confidence: 87%
“…Cationic molecules including polyamines induce actin bundles (Muhlrad et al 2011) and specific growth of actin-enriched lamellipodia in cells (Nedeva et al 2013) and promote the bundling of microtubules (Hamon et al 2011). In addition, transglutaminase-catalyzed polyamination of tubulins stabilizes microtubules in vitro and in vivo (Song et al 2013).…”
Section: Discussionmentioning
confidence: 98%